Hubungan Pengetahuan Ibu dan Riwayat Meroko Ayah dengan Kejadian Ispa pada Anak di Wilayah Puskesmas Biromaru: Penelitian - Rezki Amrullah; I Made Rio Dwijayanto; Wendi Muh. Fadhli (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Background: Acute Respiratory Infection (ARI) is an infectious disease caused by bacteria and viruses that attack the respiratory tract. The incidence of ARI in children is influenced by various factors, including demographic factors, nutritional status, environmental conditions, and exposure to cigarette smoke. This study aims to determine the relationship between maternal knowledge and paternal smoking history with the incidence of ARI in children in the working area of Biromaru Public Health Center. Methods: This study used a quantitative method with an analytical design and a cross-sectional approach. The study population consisted of all 119 parents who brought their children to the Biromaru Public Health Center between July and September, with a sample size of 41 respondents. Results: The Mann-Whitney test results showed a relationship between maternal knowledge and the incidence of ARI in children (p=0.003). The Chi-Square Continuity Correction test results showed a relationship between paternal smoking history and the incidence of ARI in children (p=0.007). Conclusion: There is a relationship between maternal knowledge and paternal smoking history with the incidence of ARI in children in the working area of Biromaru Public Health Center.